The Analysis Of Criminal Liability For Crimes Perpetrators Of The Crime Of Human Trafficking - Dharma Saputra (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Trafficking has long been a national and international issue for many nations in the world, including countries Indonesia.Trafficking secretly operates and move unlawfully. Traffickers have evolved quickly into transnational syndicates and are very subtle in trapping their victims, but have exploited them ruthlessly in various ways so that the victim becomes powerless to release. Research problems that will be discussed in this paper is the factor of crime in human trafficking, criminal liability against the perpetrators of the crime of human trafficking and efforts to prevent the crime of human trafficking. This research used normative juridical and empirical research method using secondary and primary data, library and field studies, and the were analyzed qualitatively. Data collection and processing procedures, after the data were analyzed by means of structured juridical analysis done by sorting or delivering notions of data that has been arranged systematically aiming at providing  a general overviewt o answer the problem based on the results of the research.Based on the results of research and discussion, factors  of the crime of human trafficking were rapid but uneven economic growth, poverty, family disintegration, migration, lack of education and information, culture, insentivity and gender inequality, bad influences  of war and official corruption and collaboration. Criminal responsibility of the perpetrators of the crime of human trafficking is a form of The Judge consideration of legal facts revealed in the court, where the defendant is legally and convincingly to have committed the crime of human trafficking, as stated in the indictment that violated Article 2 paragraph (1) The Law No. 21 of 2007 on the Eradication of Human trafficking. In addition, in dropping the weight and severity of criminal sanctions to the defendant, the judges ruled against NURUL ISTIQOMAH bintiSuparni imprisonment with 3 (three) years of imprisonment and a fine of Rp.120.000.000, - (one hundred and twenty million dollars) provided that if fines are not paid, it is replaced by confinement for  4(Four) months. Efforts to prevent human trafficking crime prevention (preventive) including the increase of education, dissemination of information, and the increase of surveillance is a very important factor. While enforcement efforts (repression) is the prosecution to perpetrators of the crime of human trafficking, according to the authority held by the authorities (police force, prosecutors and the courts), but considering the human trafficking is a crime that operates silently, to the general public, community institutions and NGOs, that they should take active part in uncovering this crime by providing information to the authorities if they see, witness or indicate the trafficking activities or things that can allegedly lead to the occurrence of the crime. Thus, it is expected that the Indonesian government should immediately establish minimum standards to eradicate human trafficking so that seriousness through extra measures of the government in dealing with cases of human trafficking, it is certain that it could minimize the occurrence of human trafficking in both the national and international levels. There should be improvements in trial performance, the prosecution and punishment of cases of human trafficking, including those involving women and children as victims. Checking back in the Memorandum of Understanding with the countries which became the destination of human trafficking to include the protection of victims and it is expected by the Act No. 21 of 2007 on the Eradication of Human trafficking implemented and properly applied especially to law enforcement officials, the police officers, prosecutors and the judge so that the parties involved as perpetrators and victims can be done in a fair legal process